A simple pyrazine based ratiometric fluorescent sensor for Ni2+ ion detection. (February 2020) - Dhanushkodi, Mohanasundaram; Vinoth Kumar, Gujuluva Gangatharan; Balachandar, Balakrishnan Kalaiarasan; Sarveswari, S.; Gandhi, Sivaraman; Rajesh, Jegathalaprathaban
Abstract: Herein, we checked if the existing mercury sensor (R ) could be applied for the detection of Ni 2+ ion in both colorimetrically as well as fluorimetrically. The fluorescent detection limit for Ni 2+ ion is as low as 8.62 × 10 −7  M, which is lower than the guideline for drinking water (1.2 × 10 −6  M) by American Environmental Protection Agency (EPA). All the findings were theoretically supported using Density Functional Theory (DFT) studies. The sensing ability of R for Ni 2+ was effectively applied to real water samples. Based on the color changing and spectral response in this method, we investigated molecular logic gates with single and dual input signal amplification by employing chemical input (Ni 2+ ) and light input (UV). Furthermore, test kits containing R were constructed, which could perform as a suitable and competent analysis for "in-the-field" measurement of Ni 2+ . Graphical abstract: Image 1 Highlights: The synthesized sensor has selectively detect Ni 2+ ion in both colorimetrically and fluorimetrically. This sensor has used for the construction of molecular logic gates with single input and double input by Ni 2+ and UV. DFT calculations were theoretically supported the sensing mechanism. The proposed sensor has potentially useful to the application of fluorescence imaging an "in-the-field measurement" of Ni 2+ .